Risk Management for 4-H Youth Development: Volunteer and Youth Protection - Paula M. Davis; Dale Pracht; Stefanie Prevatt; Janet Psikogios; Kate Fogarty; Jean Hink; Marilyn Norman (EDIS)
This 3-page publication is one in the series Risk Management for 4-H Youth Development Work. It focuses on the basic overall precautions that need to be taken by everyone involved with 4-H. Written by Paula Davis, Dale Pracht, Stefanie Prevatt, Janet Psikogios, Kate Fogarty, Jean Hink, and Marilyn Norman and published by the UF/IFAS 4-H Youth Development Department, September 2018. https://edis.ifas.ufl.edu/4h393